Multimodal analysis of pretreated biomass species highlights generic markers of lignocellulose recalcitrance - Herbaut, Mickaël (Biotechnol Biofuels, 2018)
BACKGROUND: Biomass recalcitrance to enzymatic hydrolysis has been assigned to several structural and chemical factors. However, their relative importance remains challenging to evaluate. Three representative biomass species (wheat straw, poplar and miscanthus) were submitted to four standard pretreatments (dilute acid, hot water, ionic liquid and sodium chlorite) in order to generate a set of contrasted samples. A large array of techniques, including wet chemistry analysis, porosity measurements using NMR spectroscopy, electron and fluorescence microscopy, were used in order to determine possible generic factors of biomass recalcitrance. RESULTS: The pretreatment conditions selected allowed obtaining samples displaying different susceptibility to enzymatic hydrolysis (from 3 up to 98% of the initial glucose content released after 96 h of saccharification). Generic correlation coefficients were calculated between the measured chemical and structural features and the final saccharification rates. Increases in porosity displayed overall strong positive correlations with saccharification efficiency, but different porosity ranges were concerned depending on the considered biomass. Lignin-related factors displayed highly negative coefficients for all biomasses. Lignin content, which is likely involved in the correlations observed for porosity, was less detrimental to enzymatic hydrolysis than lignin composition. Lignin influence was highlighted by the strong negative correlation with fluorescence intensity which mainly originates from monolignols in mature tissues. CONCLUSIONS: Our results provide a better understanding of the factors responsible for biomass recalcitrance that can reasonably be considered as generic. The correlations with specific porosity ranges are biomass species-dependent, meaning that enzymes cocktails with fitted enzyme size are likely to be needed to optimise saccharification depending on the biomass origin. Lignin composition, which probably influences its structure, is the most important parameter to overcome to enhance enzymes access to the polysaccharides. Accordingly, fluorescence intensity was found to be a rapid and simple method to assess recalcitrance after pretreatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13068-018-1053-8) contains supplementary material, which is available to authorised users.